The Effect Of Physical Treatment And Fermentation On Chemical And Nutritional Composition Of Malaysian Rubber Seed - Dongoran, Eka Hamonangan (2011)

(untitled)
Rubber seed (Hevea brasiliensis) as a by-product from rubber plantations contains nutritive values that can be harnessed as food for human, feed for animals or fuel for energy. Chemical analyses and the highest yield from the screw pressed rubber oil and rubber meal have been done in this study. The study continued to evaluate chemical analyses from the best conditions of press parameters, detoxification treatments to reduce HCN content on rubber seed using some methods (heat treatment, storage, soaking, and fermentation). Results showed that rubber seed can alternatively be considered as potential feed stuff and good companion for maize as feed for animal. Essential amino acid of rubber seed showed rubber seed high in Valine but low in Methionine. Fermentation process is the best result to reduce HCN content among other treatments. There were significant differences among detoxification treatments, which is the fermentation process reduced more HCN content comparing other treatments.